Comparing different approaches for modeling the vertical motion of the EC 135 - Seher-Weis, S. (My University, 2014)
Helicopters like the EC135 with its bearingless main rotor design feature large equivalent hinge offsets of about 10 %, significantly higher than conventional rotor designs and leading to improved maneuverability and agility. For such a helicopter, the fuselage and rotor responses become fully coupled and the quasi-steady assumption using a 6-DoF rigid-body model state space description and approximating the neglected rotor degrees of freedom by equivalent time delays is not suitable. Depending on the intended use of the model, the accurate mathematical description of the vertical motion for these configurations requires an extended model structure that includes inflow and coning dynamics. The paper first presents different modeling approaches and their relationship. Next, identification results for the DLR EC135 are presented for a model that only describes the vertical motion excluding coupling to the other axes. Here, the differences between the modeling approaches and the respective deficits are explained. Next, the modelling approach most widely used in the rotorcraft identification literature is extended to account for hinge offset. In addition, some model parameters are estimated instead of fixing them at their theoretical predictions which leads to a very good match with EC135 flight test data. Results for a complete model of the EC135 including flapping, coning/inflow, and regressive lead-lag are shown as a final result.